DESIGN OF WELDED STRUCTURES (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article analyzes the process of designing welded structures and provides information about its basic principles, methodologies, and welding methods. The article covers important aspects of the welding process - strength, stability, energy efficiency and quality. It also considers possible problems in the design of welded structures and methods for their solution. Detailed information is provided on welding methods, including technologies such as argon, electric, spot, micro, reverse and laser welding. This article provides the knowledge necessary for the effective design of welded structures in industrial and architectural fields.